2009
DOI: 10.1007/s10566-009-9081-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sleep in Childhood Psychiatric Disorders

Abstract: Although sleep problems often comprise core features of psychiatric disorders, inadequate attention has been paid to the complex, reciprocal relationships involved in the early regulation of sleep, emotion, and behavior. In this paper, we review the pediatric literature examining sleep in children with primary psychiatric disorders as well as evidence for the role of early sleep problems as a risk factor for the development of psychopathology. Based on these cumulative data, possible mechanisms and implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 101 publications
2
80
1
Order By: Relevance
“…Overall, discrepancies between studies may be partly explained by Sleep, emotional and behavioural problems in youth 11 differences in the age of participants and severity of depression symptoms (for a review, see elsewhere). 32 Studies using other objective sleep assessment methods shed additional light on this topic. For example, an actigraphic study of rest-activity cycles in children with MDD found that in comparison to controls these children present damped circadian amplitude and lower light exposure and daytime activity levels.…”
Section: Sleep and Depressionmentioning
confidence: 99%
“…Overall, discrepancies between studies may be partly explained by Sleep, emotional and behavioural problems in youth 11 differences in the age of participants and severity of depression symptoms (for a review, see elsewhere). 32 Studies using other objective sleep assessment methods shed additional light on this topic. For example, an actigraphic study of rest-activity cycles in children with MDD found that in comparison to controls these children present damped circadian amplitude and lower light exposure and daytime activity levels.…”
Section: Sleep and Depressionmentioning
confidence: 99%
“…At the same time, sleep disruption results in decreased emotion regulation (e.g., Sagaspe et al, 2006) and increased pain sensitivity (Roehrs, Hyde, Blaisdell, Greenwald, & Roth, 2006). Thus, sleep disruption may exacerbate emotional, behavioral, attentional, and somatic symptoms, further interfering with sleep quality (Alfano & Gamble, 2009). Given that sleep behaviors in young children reflect early attempts to self-regulate (Alfano & Gamble, 2009), persistent sleep disruption may represent a prodromal form of emotion dysregulation, sharing neurological and hormonal circuitry (Leahy & Gradisar, 2012).…”
mentioning
confidence: 99%
“…Reactive aggression has been repeatedly found to be associated with symptoms of anxiety (e.g., Card and Little 2006;Fite et al 2010;Seah and Ang 2008;Xu and Zhang 2008), and anxiety symptoms are associated with sleep difficulties (Becker 2014;Manni et al 1997;Sarchiapone et al 2014). These sleep difficulties are likely the result of the physiological and psychological arousal experienced as a result of these symptoms (Alfano and Gamble 2009;Dahl 2006;El-Sheikh and Buckhalt 2005;Gregory and Sadeh 2012). In contrast, proactive aggression was not associated with anxiety and was unrelated to sleep problems once also considering the variance associated with reactive aggression.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, there is strong evidence to suggest that anxiety is associated with sleep difficulties (Alfano and Gamble 2009;Becker 2014;Manni et al 1997;Sarchiapone et al 2014). For example, among anxious youth, clinically-significant sleep problems were reported by 85 % of parents (Alfano et al 2010).…”
Section: Aggression and Sleep Problemsmentioning
confidence: 99%
See 1 more Smart Citation